A prática do professor de matemática em classes de recuperação de ciclo II no regime de progressão continuada do estado de São Paulo - Felix, Marcos da Silva [UNESP] (2007)
This work focuses on the Mathematics teacher's practice in the System of Continuing Progression of the State of São Paulo. The groups of students involved in this research are of those who failed the eighth grade of primary education and are now doing extra class studies through the Teaching and Learning Project of Cycle II at the state of São Paulo. The objective of this research is to identify and to show the actions and the problems related to the pedagogical practice of the Mathematics teacher and to check if this actions propitiate, or not, advances in the process of learning of the these specials groups of students that are at the end of the basic education. This study also tried to show the daily routine of the Mathematics teacher who works in such particular classes and how they think, act and work with the interference of an institution as well as the relationships inside it. A qualitative approach was used in this research and the processes of investigation utilized were: documental analysis focused on the analysis of the already mentioned Project, application of questionnaire, class observation and interviews with the teachers. The analysis of the collected data revealed the teacher's disbelief about the project, mainly about the way that it was planed, promoted and implemented. The absence of schools's infrastructures and of others institutional conditions were highlighted as an obstacle for the project's success. One of the pointed conditions is referred to the way how schools are still working from the administrative view, similar to the series schools. Some of the investigated Mathematics teacher's revealed compromising with the project and showed as singular practice to work with these special students and even without the ideal conditions they arrived to guarantee learning conditions for them. It concludes that only with State, teachers and schools's compromising, students's learning conditions can be guarantee.